Terminal uranium(V)-nitride hydrogenations involving direct addition or Frustrated Lewis Pair mechanisms - Chatelain, Lucile (Nat Commun, 2020)
Despite their importance as mechanistic models for heterogeneous Haber Bosch ammonia synthesis from dinitrogen and dihydrogen, homogeneous molecular terminal metal-nitrides are notoriously unreactive towards dihydrogen, and only a few electron-rich, low-coordinate variants demonstrate any hydrogenolysis chemistry. Here, we report hydrogenolysis of a terminal uranium(V)-nitride under mild conditions even though it is electron-poor and not low-coordinate. Two divergent hydrogenolysis mechanisms are found; direct 1,2-dihydrogen addition across the uranium(V)-nitride then H-atom 1,1-migratory insertion to give a uranium(III)-amide, or with trimesitylborane a Frustrated Lewis Pair (FLP) route that produces a uranium(IV)-amide with sacrificial trimesitylborane radical anion. An isostructural uranium(VI)-nitride is inert to hydrogenolysis, suggesting the 5f(1) electron of the uranium(V)-nitride is not purely non-bonding. Further FLP reactivity between the uranium(IV)-amide, dihydrogen, and triphenylborane is suggested by the formation of ammonia-triphenylborane. A reactivity cycle for ammonia synthesis is demonstrated, and this work establishes a unique marriage of actinide and FLP chemistries.